Community perspectives on food security and dietary diversity among rural smallholder farmers: A qualitative study in central Uganda - Nabuuma, Deborah; Ekesa, Beatrice; Faber, Mieke; Mbhenyane, Xikombiso (Elsevier, 2021)
Smallholder farmers produce majority of food in developing countries yet continue to be vulnerable to poverty, food insecurity, limited diet quality and diversity, malnutrition, and face various production challenges. Though quantitative studies have explored determinants of dietary diversity among farmers, this data can be further enriched with farmer experiences and perspectives of whether and how these factors affect dietary diversity to inform intervention design and implementation. A qualitative study was conducted among rural smallholder farmers in Kiboga district, Central Uganda with 28 participants in eight focus group discussions (four groups with men and four groups with women). The results showed that both men and women were concerned about food security and dietary diversity and viewed household food production as pivotal to food security. Purchase of food was affected by prices, household income, distance to markets and food diversity in the accessed markets. Major determinants of dietary diversity included household food production, agricultural and nutrition knowledge and awareness, information access and use, household income, and time. Poor perception towards meetings, insufficient nutrition information, skills and training were also noted. Gender influences and differences noted were concerned with allocation and use of harvested food and income within the household; more men than women having a poor perception towards meetings/trainings; and women having limited time for agricultural and nutrition practices that support dietary diversity. From the results, efforts to improve dietary diversity should address the food security and production challenges faced; support income generation whether on- or off-farm and market access to diverse foods; use designs that address gender issues and are labor and time sensitive; and include capacity building in nutrition and practices that support access to and utilization of diverse food baskets, and social behavior change strategies.